2016
DOI: 10.1186/s12884-016-1052-3
|View full text |Cite
|
Sign up to set email alerts
|

Audit of a program to increase the use of vacuum extraction in Mulago Hospital, Uganda

Abstract: Background: Prolonged second stage of labour is a major cause of perinatal and maternal morbidity and mortality in low-income countries. Vacuum extraction is a proven effective intervention, hardly used in Africa. Many authors and organisations recommend (re)introduction of vacuum extraction, but successful implementation has not been reported. In 2012, a program to increase the use of vacuum extraction was implemented in Mulago Hospital, Uganda. The program consisted of development of a vacuum extraction guid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
52
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(56 citation statements)
references
References 29 publications
2
52
2
Order By: Relevance
“…Where AVD has been dropped from pre‐service or in‐service B‐EmOC training, we should understand why this has occurred. We need to learn from successful AVD reintroduction pilots in Tanzania (health centres upgraded by the World Lung Foundation's Maternal Health project to provide caesarean delivery and AVD), Uganda at the Mulago National Referral Hospital, and Ecuador at the Sotomayor Hospital in Guayaquil . Finally, much is riding on the Odon device trials that are underway; the device is a low cost technological innovation that can be used without electricity by midwives.…”
Section: Discussionmentioning
confidence: 99%
“…Where AVD has been dropped from pre‐service or in‐service B‐EmOC training, we should understand why this has occurred. We need to learn from successful AVD reintroduction pilots in Tanzania (health centres upgraded by the World Lung Foundation's Maternal Health project to provide caesarean delivery and AVD), Uganda at the Mulago National Referral Hospital, and Ecuador at the Sotomayor Hospital in Guayaquil . Finally, much is riding on the Odon device trials that are underway; the device is a low cost technological innovation that can be used without electricity by midwives.…”
Section: Discussionmentioning
confidence: 99%
“…Although vacuum extraction is used regularly, and the hospital has a protocol with indications, the decision regarding mode of delivery depends not only on clinical factors but also on the doctor's personal preference and expertise, as well as the availability of theater and vacuum equipment. Many women undergoing cesarean delivery at Mulago National Referral Hospital could be eligible for vacuum extraction …”
Section: Methodsmentioning
confidence: 99%
“…Indications for this approach include fetal distress, prolonged second stage of labor, maternal exhaustion, or the need to avoid expulsive efforts among women with conditions such as heart failure or severe anemia . Although vacuum extraction can reduce maternal mortality from hemorrhage and sepsis—as well as perinatal mortality from birth asphyxia—use of this method has almost disappeared from obstetric practice in many LMICs . One study found that instrumental vaginal delivery was not used in almost half of 1728 Sub‐Saharan African hospitals, with usage rates below 1% in the remaining centers.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations